BCL2 drives castration resistance in castration-sensitive prostate cancer by orchestrating reciprocal crosstalk between oncogenic pathways - Rahim Hirani; Subhiksha Nandakumar; Nabila Zaman; Prathiksha Prabhakaraalva; Sarah Ann King; Teja Muralidhar Kalidindi; Romina Ghale; Sai Harisha Rajanala; Deborah C. Fidele; Elisa De Stanchina; Gwo-Shu Mary Lee; Mary Ellen Taplin; et al. (Cell Reports)
Summary: Progression following androgen-deprivation therapy (ADT) and the development of castration resistance is the leading cause of death among prostate cancer patients. Since there is currently a lack of known driver alterations associated with ADT resistance in castration-sensitive prostate cancer (CSPC), we investigated the critical role of crosstalk between cell signaling networks in early castration resistance. Our preclinical experiments and analyses of RNA sequencing data from clinical trials revealed nearly universal upregulation of BCL2 after ADT in CSPC cells. Mechanistically, our findings highlight a non-canonical function of BCL2 in orchestrating reciprocal signaling between the androgen receptor (AR)-BCL2 and phosphatidylinositol 3-kinase (PI3K) pathways, particularly upon ADT, potentially driving CSPC transformation into lethal castration-resistant prostate cancer (CRPC). Critically, our results provide a scientific rational that BCL2 inhibition should be trialed in CSPC in combination with ADT to impede or delay ADT-induced CSPC-to-CRPC transformation but may be ineffective if tested in patients who already have CRPC.